FA_PorT: um framework para sistemas portfólio-tutor baseado em agentes - Medeiros, Fábio Nicácio de (2006)
Distance Education expands the scope of the inside classroom teaching model since anybody, independent of where he lives or how much available time he has, has the opportunity to initiate or complement his studies. Considering access facility, availability and interaction resources provided, the Internet is a midia sufficiently used for Distance Education. This work has as objective the design and implementation of a framework, FA_PorT,for Portfolio-Tutoring systems coupled a Intelligent Tutoring Systems (STI) and using agents and present two applications Portfolio-Tutoring, created from the framework The FA_PorT mainly aiming the design of a model computer-based interactive learning environment for Portfolio-Tutoring systems. Each system Portfolio-Tutoring will be able to be used in the context of environment for EAD in the web. The framework proposed, aims to reuse of internal architecture (or skeleton) of a portfolio-tutoring system based on ITS and Agents, doing with that development time of a new portfolio-tutoring system will be reduced.